Implementasi Kebijakan Program Pembangunan Infrastruktur Perdesaan Terhadap Manajemen Organisasi Masyarakat Dalam Meningkatkan Pelayanan - Dasep Gumilar (Idarotuna : Journal of Administrative Science, 2022)
The aim of this research is to analyze the influence of the implementation of rural infrastructure development program policies on the effectiveness of management of local community organizations in improving public facility services for poor communities in rural areas. The methodology used in this study is qualitative analysis which uses rational rules to analyze causal-effectual relationships between variables. The results of the study show that the implementation of rural infrastructure development program policies has a positive influence on the effectiveness of management of local community organizations to improve public facility services for poor communities in rural areas